Social regulations and systems in the international agreements and their impact on the Muslim family: CEDAW as a model - Alqahs, Rawan Yahia (Journal of Humanities & Social Sciences, 2020)
The study aimed to reveal the most prominent social regulations and systems related to the role of parents in the family in the CEDAW Convention, in addition to clarifying the impact of the application of this agreement on the Muslim family. To achieve this, the descriptive analytical approach was used, and content analysis was used as a tool for analysing the articles and clauses contained in the International Convention, and the study was applied to a sample, namely the Convention on the Elimination of All Forms of Discrimination against Women, and this convention was chosen because the majority of its provisions relate to the family in addition to the accession of many Arab and Islamic countries. The study has reached a number of conclusions: The Convention does not take into account the religious and cultural specificity of some societies. The Convention also seeks to impose a secular vision on the world by abolishing the shariah provisions relating to the family. They call for the abuse of men over women in the family by changing the roles of women and men in the family and by establishing the principle of power-sharing and responsibility among them. In addition to imposing the Western family model on the world by taking away the guardianship of fathers over children. The government’s decision to amend the Law on The Rights of Women and The Rights of Women is a matter of priority. The convention also calls for women’s freedom to travel and Muslim countries have given women the right to travel without the guardian’s permission, which, if exploited negatively, will affect family construction. The study made some recommendations, the most important of which were: raising families’ awareness of family rights and duties in the light of the teachings of Islam through various media. The formation of a committee of various disciplines (political, religious and social) to study the content of international conventions of various dimensions before signing them.